Caste and punishment: the legacy of caste culture in norm enforcement - Karla Ruth Hoff; Mayuresh Kshetramade; Ernst Fehr (Institute for the Study of Labor (IZA), 2009)
Well-functioning groups enforce social norms that restrain opportunism, but the social structure of a society may encourage or inhibit norm enforcement. Here we study how the exogenous assignment to different positions in an extreme social hierarchy - the caste system - affects individuals' willingness to punish violations of a cooperation norm. Although we control for individual wealth, education, and political participation, low caste individuals exhibit a much lower willingness to punish norm violations that hurt members of their own caste, suggesting a cultural difference across caste status in the concern for members of one's own community. The lower willingness to punish may inhibit the low caste's ability to sustain collective action and so may contribute to its economic vulnerability.
urn:nbn:de:101:1-20090909555
Keywords: D02; D64; 300; Social norms; informal sanctions; third party punishment; endogenous social preferences; social exclusion; collective action; caste; Soziale Schicht; Soziale Norm; Normbefolgung; Rechtsdurchsetzung; Indien